Systematic evaluation of the evidence base on methyl tert-butyl ether supporting a lack of concern for carcinogenic hazard in humans based on animal cancer studies and mechanistic data - S.J. Borghoff; B.N. Rivera; S. Fitch; A.N. Buerger; N.Y. Choksi; A. Franzen; M.J. Vincent; T. Covington; J. Bus; E. Rushton; I.A. Lea (Current Research in Toxicology)
Methyl tert-butyl ether (MTBE) is a high-octane fuel component that helps gasoline burn cleaner and reduces automobile emissions. In 1999, the International Agency for Research on Cancer (IARC) categorized MTBE as “not classifiable” regarding human carcinogenicity. Since then, additional studies have been published that substantially added to the evidence base to examine the carcinogenic potential of MTBE in humans. A systematic literature search and review was conducted to identify mechanistic data, as well as studies investigating cancer in MTBE-exposed humans and experimental animals. Critical appraisal was performed for relevant studies with mechanistic data organized and evaluated within Key Characteristics of Carcinogens (KCCs). Three standard animal cancer bioassays showed a low incidence of hepatocellular adenomas in female mice (inhalation exposure), with renal adenomas/carcinoma (inhalation) and brain tumors (drinking water) in male rats exposed to high concentrations of MTBE. Evidence extracted from the literature demonstrate that the mechanism of male rat renal tumors does not operate in humans. Review of the strength of mechanistic data was based on activity, relevancy, and reliability, with information-dense KCC2—is genotoxic, and KCC10—alters cell proliferation, cell death, and nutrient supply, together supporting that MTBE is unlikely to be a carcinogenic hazard to humans.